Giant Cell Tumor of Bone in Skeletally Immature Patients - A Clinical Perspective - Sharma, Vipin (J Orthop Case Reports, 2015)
INTRODUCTION: Giant cell tumors of skeleton are very rare in pediatric and adolescent population. Here we report two cases-one a fifteen year old child with swelling distal humerus and another a case of a thirteen year old child with pain and swelling proximal tibia. CASE REPORT: A fifteen year old child presented to department of orthopedics of our institute with complaint of difficulty in moving upper limb and swelling distal humerus. Another patient who was a 13 years old male had painful ambulation and swelling in upper tibia. MRI followed by core needle biopsy was done in both the patients confirming the mass to be giant cell tumor which is quite rare in this age group. First patient was managed by wide excision and total elbow replacement and second one by curettage, cementation and augmentation with plate-screw construct. CONCLUSION: Giant cell tumour of skeleton is highly uncommon in pediatric age group. It should be considered as one of the differential diagnosis of epiphyseo metaphyseal lesions in pediatric population in spite of its rarity.